How at risk high school learners with SEN view and feel about inclusion - Pride, Marie (2017)
This qualitative research study presents the experiences and views of six at risk high school students with SEN across years 7-12 learning in two mainstream non-selective inclusive government schools on a small Caribbean Island. Inclusion as a concept is concerned with the elimination of all forms of exclusionary practices and barriers to learning in education; inclusion aims to increase participation and equal opportunities in the education of all children and young people in a community. The focus of this study is to critically explore the vision for inclusion on a small Caribbean Island following subscription to the ideals of the 1994 Salamanca Statement calling for the prioritization of inclusive education (Mitchell, 2014). A calling that continues to permeate policy and practice on the island to this day (Thomas & Vaughan, 2004) with the model of mainstreaming operating as the norm, in most countries (Hannell, 2014). The study commences with a literature review of the country’s policies and practices for promoting inclusion along with a critique of inclusion as a policy aim. The literature review explores the paradox and tensions of simultaneously developing inclusion within a standards driven system of education (Ainscow et al., 2006). The findings of this research indicate that students feel that their mainstream educators are paramount in aiding their success. Additionally, their success hinges on positive relationships and displayed feelings of care, which are tied to a positive school culture. The findings portray that inclusion units are seen as central for the at risk student’s academic success and emotional coping. Inclusion units provide support that is otherwise lacking in some of their mainstream classrooms. Students indicate high levels of satisfaction with the bespoke interventions provided for them.